"Keeping Vigil" and the Response of a Believer to Grief and Suffering. Issue 2 (7th November 2017) - Sabak, James G.
Abstract : The phenomenon of organizing a civic candlelight vigil in the face of violence and tragedy, while striking and powerful in addressing the moment, can be also religiously ambiguous in some circumstances, and insufficiently therapeutic in others. Keeping vigil in the Christian tradition is markedly different from its contemporary expressions. This article explores and evaluates—through the use of contemporary examples and the psychological and ritual analyses of Gotthard Booth and Victor Turner—the purpose and goals of vigils held in the public square with the nature and impact of keeping vigil in the Christian tradition, especially as celebrated in the Easter Vigil. This expository and diagnostic study suggests that a full expression of keeping vigil serves as an articulation of how believers are challenged to confront pain and suffering with a more profound theological and liturgical response that stands in stark contrast to contemporary cultural and social mechanisms.